AB1190 Macrophage activation syndrome as the presenting manifestation of systemic juvenile arthritis: Unicenter study of clinical features and outcome in 12 patients. (23rd January 2014) - Russo, R.; Katsicas, M.M.
Abstract : Background: Macrophage activation syndrome (MAS) is a serious event in the course of systemic juvenile idiopathic arthritis (SJIA). MAS may be the initial presentation of the disease in some patients, even before the articular symptoms are present, making diagnosis difficult (1). The outcome of such patients Is not known. Objectives: to describe the clinical features and outcome of a series of patients with SJIA who presented with MAS. Methods: retrospective review of clinical records. Patients who fulfilled the criteria of Ravelli et al. (2) for classification of MAS in SJIA were included. Recorded features were clinical, hematological and serological manifestations at MAS episode; outcome of MAS; type of disease course, occurrence of remission, radiological damage, disability (CHAQ ≥0.75), need for biologics, during SJIA course. Values are expressed as medians. Results: MAS developed as the initial manifestation in 12/35 (35%) of SJIA patients who developed MAS ever during the period 1995-2011. Age at presentation was 38 months, 8 girls, 4 boys. MAS developed 9.5 months before the onset of joint symptoms in 4 patients. All children showed fever, hepatomegaly, and splenomegaly. Fixed rash was observed in 8, adenomegaly in 8, edema in, hemorrhage in 5, CNS manifestations in 5, pulmonary infiltrates in 5, and jaundice in 3 patients each. Lowest values for hemoglobin: 74.5 g/L, WBC: 2.26×10 9 /L, platelet count 74×10 9 /L, ESR 19 mm/h, fibrinogen 123 mg/dl; highest SGOT 364 IU/L, SGPT 125 IU/L, triglycerides 230 mg/dl. Coagulopathy developed in 9 children. Bone marrow biopsy was obtained in 8 patients: 5 samples showed hemophagocytosis. A trigger infection was detected in 3 children: EBV, HAV, and CMV. Patients received steroids (12), cyclosporine (4), IVGG (3), or etoposide (2). Three patients were admitted to the ICU, and 2 of them died from multiorgan failure. These 2 patients were the older of this cohort (15 and 16 years old respectively). MAS resolved completely in the remaining 10 patients, who have been followed for 6.5 years since. No MAS-related sequelae were observed in them. SJIA followed different courses: 4 patients eventually reached inactivity and remission, while 6 patients had a persistently active disease course, with a destructive arthritis, subsequent persistent disability and radiological damage in 3 of them. In total, 6 children needed the use of biologics. MAS recurred in 2 of these latter patients at 1 and 4 years after the initial episode, and it resolved completely in both cases. Conclusions: MAS occurring at SJIA onset evidences typical characteristics. It may precede the onset of arthritis by several months. Mortality is similar to the one observed in patients with MAS during SJIA disease course. Patients who had MAS at onset may follow a benign, remitting course or a more persistent and destructive pattern. Increased awareness may allow earlier diagnosis and treatment in these patients. References: Avcin T et al. Macrophage activation syndrome as the presenting manifestation of rheumatic disease in childhood. J Pediatr 2006. Ravelli A et al. Preliminary diagnostic guidelines for macrophage activation syndrome complicating systemic juvenile idiopathic arthritis. J Pediatr 2005 Disclosure of Interest: None Declared